Derivatives of α,α-Aryl Naphthalimide Nitriles as Fluoride Ion Sensors: Convenient Precursors for the Synthesis of Aryl Naphthalimide Ketones - Chen, Jinju; Liu, Chuanxiang; Guan, Fengjie; Zhang, Chuanxiu; Ji, Kai; Wang, Xinyu; Xu, Min; Wu, Fanhong (Synlett, 2015)
A facile and efficient SNAr procedure involving the displacement of activated naphthalimide bromides with the anions of substituted aryl acetonitriles was developed for the preparation of α,α-aryl naphthalimide nitrile derivatives, which can be used as fluoride ion sensors and convenient precursors for the synthesis of aryl naphthalimide ketones based on fluoride-induced deprotonation followed by autoxidative decyanation.
Keywords: substituent effects; supramolecular chemistry; molecular recognition; nucleophilic aromatic substitution; oxidation